Bioprospecting of exopolysaccharide from marine Sphingobium yanoikuyae BBL01: Production, characterization, and metal chelation activity. (March 2021) - Kant Bhatia, Shashi; Gurav, Ranjit; Choi, Yong-Keun; Choi, Tae-Rim; Kim, Hyun-joong; Song, Hun-Suk; Mi Lee, Sun; Lee Park, Sol; Soo Lee, Hye; Kim, Yun-Gon; Ahn, Jungoh; Yang, Yung-Hun
Graphical abstract: Highlights: Sphingobium yanoikuyae BBL01 was isolated from marine habitat. Strain able to produce a heteropolysaccharides i.e., 2.63 ± 0.02 g/L EPS. Exopolysaccharide was composed of seven different monosaccharides units. Exopolysaccharide was thermally stable up to 233 °C. EPS showed emulsifying, flocculating, and metal chelating activity. Abstract: In the present study, an exopolysaccharide (EPS)-producing bacterial strain was isolated from the Eastern Sea (Sokcho Beach) of South Korea and identified as Sphingobium yanoikuyae BBL01 . Media optimization was performed using response surface design, and a yield of 2.63 ± 0.02 g/L EPS was achieved. Purified EPS produced using lactose as the main carbon source was analyzed by GC–MS and found to be composed of α-D-xylopyranose (28.6 ± 2.0%), β-D-glucopyranose (21.0 ± 1.6%), α-D-mannopyranose (18.5 ± 1.2%), β-d -mannopyranose (13.1 ± 1.4%), β-D-xylopyranose (10.2 ± 2.1%), α-d -talopyranose (5.9 ± 1.1%), and β-d -galacturonic acid (2.43 ± 0.8%). Interestingly, different carbon sources (glucose, galactose, glycerol, lactose, sucrose, and xylose) showed no effect on EPS monomer composition, with a slight change in the mass percentage of various monosaccharides. Purified EPS was stable up to 233 °C, indicating its possible suitability as a thickening and gelling agent for food-related applications. EPS also showed considerable emulsifying, flocculating, free-radical scavenging, and metal-complexion activity, suggesting various biotechnological applications.